Bathymetry of the Norwegian-Greenland and western Barents seas / bathymetry compiled by R.K. Perry . [and others] - Perry, Robert K. (Geological Society of America, 1977)
Depths shown by gradient tints and contours.; Includes ancillary maps "Aeromagnetic profiles" and "Physiographic provinces," sheet index to bathymetric enlargements, and notes.; The location of ship tracks from which soundings were obtained for this study are shown on the reverse side of this chart for obverse viewing on verso.; Map shows earthquake epicenters.; Includes bibliographical references. Color; 1:2,333,230